2020
DOI: 10.1155/2020/2907293
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Conventional Swallowing Therapy in Acute Stroke Patients with Dysphagia

Abstract: Background. Dysphagia is a common problem in acute stroke patient. Aspiration pneumonia increases in this group. Swallowing therapy is immediately conducted in a stable stroke patient. An effectiveness of our program has not been determined. Objective. To determine an effectiveness of conventional swallowing therapy in acute stroke patients with dysphagia. Methods. We retrospectively reviewed data from medical records of acute stroke patients with dysphagia who participated a swallowing therapy from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In our study, we found most of our patients' pharyngeal phase of swallowing was affected. This finding was similar to the studies of Martino et al 42 and Logemann et al 41 Similar finding was also reported by Priya et al 47 The baseline VDS score was 54.43 ± 11.23, quite higher than a study done by Park et al, 48 who included unilateral hemispheric stroke and post 1-month stroke. Pyriform fossa residue has been given a higher value (13.5) in the VDS score.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we found most of our patients' pharyngeal phase of swallowing was affected. This finding was similar to the studies of Martino et al 42 and Logemann et al 41 Similar finding was also reported by Priya et al 47 The baseline VDS score was 54.43 ± 11.23, quite higher than a study done by Park et al, 48 who included unilateral hemispheric stroke and post 1-month stroke. Pyriform fossa residue has been given a higher value (13.5) in the VDS score.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that there was a significant improvement in swallowing in acute stroke patients with conventional swallowing therapy, which includes Mendelsohn maneuver and head rotation to paretic side. 48…”
Section: Introductionmentioning
confidence: 99%
“…Forty-two percent of patients with tube dependent change to total oral intake. The study concluded that Conventional swallowing therapy is an effective treatment in acute stroke with dysphagia [12] .…”
Section: Introductionmentioning
confidence: 95%
“…Brain controls most of the voluntary and involuntary activities of the human body. The major problem of cerebrovascular accident is the paralysis of swallowing muscles leading to swallowing difficulty which is known as dysphagia [1] . Approximately 90% of CVAs were attributed to 10 risk factors that are preventable (hypertension, regular physical inactivity, high apolipoprotein B/A1 ratio, insufficient diet quality, increased waist/hip ratio, psychosocial factors, current smoking, cardiac causes, heavy alcohol consumption, and diabetes mellitus [2] .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The effectiveness of behavioral therapy varies widely due to multiple factors including the underlying physiologic impairment, severity of deficits, type of intervention, and therapeutic engagement. [15][16][17][18][19][20][21][22][23][24] One potential explanation of this variation is an absence of sensitive, quantitative tools to monitor progress. There is a plethora of evidence suggesting that when patients are compliant and accurately execute therapy plans, swallowing outcomes improve.…”
Section: Introductionmentioning
confidence: 99%